FORMALIZATION OF MINING RIGHTS IN THE EAST AFRICAN COMMUNITY; CADASTRE PERSPECTIVE ON ARTISANAL MINING RIGHTS - George Odhiambo Konguka; Samson OkothAyugi (African Journal on Land Policy and Geospatial Sciences, 2022)
Context and background